Research on Strategic selection of Chinese Commercial Banks under the Entry of Foreign Banks - Xie, Ting (2007)
The foreign banks have the fully market access and the limitations on arena and customer will be totally eliminated since December 11th, 2006. The foreign banks have intense competition on arena, customer, human resources and other fields with Chinese commercial banks. Therefore, it is a principle question of how to select strategies.